Analisis Manajemen Sekuriti di Badan Pengembangan Sumber Daya Manusia (BPSDM) Provinsi Jawa Barat - Rizky Hakiki; Ahmad Taufik Riyadi Sanusi; Muhammad Ardika Putra Maulana; Muhammad Akmal Dzulfikar; Muhammad Fahrel Aditya (Journal of Informatic and Information Security, 2024)
This report presents an analysis of security management at the West Java Province Human Resources Development Agency (BPSDM) with the aim of evaluating and improving the existing information security system. In the era of globalization and advances in information technology, information security has become an important part of the economy, especially in the field of natural resource management. This research will use qualitative and quantitative approaches to collect data through interviews, questionnaires, observations and document studies. The survey found that although employees have a good understanding of the information security policy, there are challenges in its implementation, including lack of resources, inadequate training and barriers to change. Suggested recommendations include enhancing information security training programs, better policy implementation, strengthening access controls, and periodic evaluation of security management practices. We hope this report can make a positive contribution to the sustainable and secure management of natural resources.